An assessment of selected public secondary school libraries in the Division of Quezon City - Torres, Susana De Leon (Institute of Library and Information Science, University of the Philippines Diliman, 2003)
This study aimed to assess the current status of selected secondary public school libraries in Quezon City. Specifically, it aimed to assess the selected public secondary school library in terms of collection, services, facilities, personnel and budget. In order to gather the necessary data for this study, survey questionnaires were administered to librarians, faculty members and students of the following secondary public schools: 1) Juan Sumulong High School (JSHS), 2) Camp General Emilio Aguinaldo High School (CGEAHS), 3) Camp Crame High School (CCHS), 4) Ramon Magsaysay (Cubao) High School (RM(C)HS), 5) Lagro High School (LHS), 6)Ernesto Rondon High School (ERHS), 7)New Era High School (NEHS), 8) E Rodriguez Jr. High School (ERJHS), 9) Judge Juan Luna High School (JJLHS) and 10) Quirino High School (QHS). Respondents for this study constituted 10 librarians, 100 faculty members (10 per school) and 200 students (20 students per school-5 students from each year level) from the 10 selected secondary public schools. Stratified random sampling was used to select the respondents for the study. JSHS and QH libraries have the most liberal space allocation among the ten selected school libraries, whereas ERHS and LHS libraries have the smallest space allocation.